2023
DOI: 10.25220/wnj.v06.i2.0001
|View full text |Cite
|
Sign up to set email alerts
|

Fueling growth and preventing stunting: the role of animal protein in achieving optimal nutrition - Indonesia's National Nutrition Day 2023 Theme

Abstract: Poor linear growth, currently defined as inadequate height to growth standards defined by the World Health Organization (WHO), is still a major problem in low-middle-income countries (LMICs) including Indonesia. The national survey results from 36.8% in 2007 to 30.8% in 2018 showed small differences in under-five years old children with height-for-age-Z-score less than -2 standard deviation (HAZ < -2 SD) from the growth reference or stunted.1  Though the Indonesian Nutrition Status Survey results showed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…If the intervention is carried out in stages each month, the mother's knowledge will improve significantly. Several studies [32][33][34][35][36][37][38][39][40] have found that offering education to moms has a substantial influence. In this study, health education was delivered in four stages over four months.…”
Section: Discussionmentioning
confidence: 99%
“…If the intervention is carried out in stages each month, the mother's knowledge will improve significantly. Several studies [32][33][34][35][36][37][38][39][40] have found that offering education to moms has a substantial influence. In this study, health education was delivered in four stages over four months.…”
Section: Discussionmentioning
confidence: 99%